An interesting case of faecolith intestinal obstruction - Agrawal, Sujan Narayan; Joshi, Vivek Kumar; Mittal, Vineet (International Surgery Journal, 2017)
Intestinal obstruction is a common presentation in surgical wards. Faecolith causing intestinal obstruction are of rare occurrence that too in small bowel. We are herewith presenting a case of intestinal obstruction in small bowel due to Faecolith. It was treated by exploratory laprotomy and removal of Faecolith by enterostomy. This case is presented because of its rarity and emphasis on good history taking and pre-operative workup.